2023
DOI: 10.3390/su151411014
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization, Carbon Productivity and Technological Innovation in Manufacturing—Evidence from China

Abstract: Manufacturing is one of the vital carbon emission sources in China; its carbon emission reduction and carbon productivity improvement are the keys to the successful realization of “carbon peaking and carbon neutrality”. This paper investigates the impact of regional manufacturing digitalization on carbon productivity based on a panel data set covering 30 provinces in China over time from 2013 to 2020. We applied the mixed Ordinary Least-Squares (OLS) regression effect model and instrumental variable method, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The other is the impact of the digitalization of HCM on its carbon emissions. Previous studies, using regression analysis, have pointed out that the digital transformation of HCM can reduce carbon emissions, mainly through fostering green technology and product innovation [28] and improving enterprise energy use efficiency [29]. Shabani and Shahnazi [30], based on Iranian data, found that the digitization of HCM had a positive impact on its direct carbon emissions.…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…The other is the impact of the digitalization of HCM on its carbon emissions. Previous studies, using regression analysis, have pointed out that the digital transformation of HCM can reduce carbon emissions, mainly through fostering green technology and product innovation [28] and improving enterprise energy use efficiency [29]. Shabani and Shahnazi [30], based on Iranian data, found that the digitization of HCM had a positive impact on its direct carbon emissions.…”
Section: Literature Review and Theorymentioning
confidence: 99%